The Fourteenth Marcel Grossmann Meeting 2017
DOI: 10.1142/9789813226609_0225
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic representation of a cosmic scalar field

Abstract: We derive the fluid equations governing the evolution of a cosmic scalar field (e.g. an axion field) described by the Klein-Gordon-Einstein equations in an expanding universe. We consider the nonrelativistic limit where the Klein-Gordon-Einstein equations reduce to the Schrödinger-Poisson or to the Gross-Pitaevskii-Poisson equations. Our quantum hydrodynamic equations generalize the classical hydrodynamic equations of the cold dark matter model by including a quantum force and a pressure force due to the selfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…This allowed us to analyze the cosmological evolution of the Jeans scales. We have stressed the analogy, previously noticed in [67], between the Jeans mass-radius relation M J (λ J ) in the linear regime of structure formation and the mass-radius relation M (R) of boson stars and dark matter halos in the nonlinear regime of structure formation (this analogy will be further developed in a future work [209]). We have considered different limits (ultrarelativistic, nonrelativistic, noninteracting, TF, nongravitational) and we have given precise conditions of validity of these different limits in terms of dimensionless parameters depending on the characteristics of the SF (mass and scattering length) and on the density of the Universe.…”
Section: Discussionsupporting
confidence: 58%
“…This allowed us to analyze the cosmological evolution of the Jeans scales. We have stressed the analogy, previously noticed in [67], between the Jeans mass-radius relation M J (λ J ) in the linear regime of structure formation and the mass-radius relation M (R) of boson stars and dark matter halos in the nonlinear regime of structure formation (this analogy will be further developed in a future work [209]). We have considered different limits (ultrarelativistic, nonrelativistic, noninteracting, TF, nongravitational) and we have given precise conditions of validity of these different limits in terms of dimensionless parameters depending on the characteristics of the SF (mass and scattering length) and on the density of the Universe.…”
Section: Discussionsupporting
confidence: 58%
“…( 146). However, it can be shown that they coincide for a spatially homogeneous SF [103,112] in certain approximations. The hydrodynamic equations ( 142)-( 145) have a clear physical interpretation.…”
Section: H Hydrodynamic Representation Of the Gross-pitaevskii Equationmentioning
confidence: 99%
“…The complete study of these relativistic hydrodynamic equations is of considerable interest but it is, of course, of great complexity. In our research papers [24,25], we have started their study in simple cases. We have checked that the hydrodynamic equations of the SFDM model reproduce the evolution of the homogeneous background obtained previously by Li et al [17] directly from the KGE equations: a stiff matter era, followed by a radiation era (for a self-interacting SF), and a matter era.…”
Section: Discussionmentioning
confidence: 99%
“…( 38). 3 However, they coincide for a homogeneous SF in the regime where the SF oscillations are faster than the Hubble expansion [24,25].…”
Section: The Gross-pitaevskii-einstein Equationsmentioning
confidence: 99%
See 1 more Smart Citation